Phase Behavior of Block Copolymer Nanocomposite Systems. Issue 9 (29th July 2018) - Diaz, Javier; Pinna, Marco; Zvelindovsky, Andrei V.; Pagonabarraga, Ignacio
Abstract: Nanocomposite materials made of block copolymer (BCP) and nanoparticles display properties which can be different from the purely polymeric matrix. The resulting material is a crossover of the original properties of the BCP and the presence of the assembled nanoparticles. A mesoscopic study using cell dynamic simulations is reported, to quantitatively describe the structural properties of such hybrid materials. The most relevant parameters are identified to be the fraction of nanoparticles in the system and its chemical affinity, while the nanoparticle size with respect to the BCP length scales plays a role in the assembly. The morphological phase diagram of the BCP is constructed for nanoparticles with chemical affinity ranging from A‐compatible to B‐compatible for a symmetric A‐B diblock copolymer. Block‐compatible nanoparticles are found to induce a phase transition due to changes in the effective concentration of the hosting phase, while interface‐compatible particles induce the appearance of two new phases due to the saturation of the diblock copolymer interface. Abstract : The phase behavior of diblock copolymer nanocomposite systems is studied in terms of the composition of the polymer blend, along with the concentration, size and chemical coating of the nanoparticles. Phase diagrams matching experimental and theoretical results, and predictions of new phases are obtained.